PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA BENGKEL MOBIL UD. SARI MOTOR DI PEKANBARU - Dzikra, Faira Medina (Sekolah Tinggi Ilmu Ekonomi Riau, 2020)
This study was conducted to determine the effect of service quality on customer satisfaction at Workshop UD. Sari Motor Pekanbaru. Population in this research is all consumer at Workshop UD. Sari Motor Pekanbaru until December 2016 amounted to 2,182 people. Samples taken as many as 96 people refer to the Slovin formula, data collection techniques in this study are questionnaires and interviews. Data analysis in this research use descriptive and quantitative analysis method. Descriptive is to compare the actual reality with theories that have to do with the problem to draw a conclusion and tabulated in the form of tables of frequency distribution. While quantitative methods of research based on the data can be calculated to produce a robust assessment. The result of simple linear regression research in this research is Y = 6.268 + 0.391X. By using t test, obtained ttabel value of 1,291 and a mean value 11,916 value tÂcount 11,916Â >ttable 1,291, which mean service quality have significant effect to consumer satisfaction at Workshop UD. Sari Motor Pekanbaru with big influence of 60,2%.